2018
DOI: 10.1016/j.msard.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

The disease burden of Multiple Sclerosis from the individual and population perspective: Which symptoms matter most?

Abstract: While HRQoL at population level is most affected by balance problems, spasticity, and depression in RRMS, the biggest HRQoL losses in PMS are caused by spasticity, paralysis, weakness, and pain. Many symptoms with the largest effects in individuals substantially contribute to the population disease burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 33 publications
3
75
0
3
Order By: Relevance
“…Zudem zeigt, in den berechneten Regressionsanalysen, der Erwerbsstatus einen Einfluss auf die HQRoL. Für weitere [20][21][22][23]. Diese drei wichtigsten Prädiktoren unserer Untersuchung zählen alle zu den sogenannten "versteckten Symptomen".…”
Section: Diskussionunclassified
“…Zudem zeigt, in den berechneten Regressionsanalysen, der Erwerbsstatus einen Einfluss auf die HQRoL. Für weitere [20][21][22][23]. Diese drei wichtigsten Prädiktoren unserer Untersuchung zählen alle zu den sogenannten "versteckten Symptomen".…”
Section: Diskussionunclassified
“…The EDSS-based disease stage categorization inherits the limitations of being mainly gait-focused and somewhat subjective in certain areas (e.g., sensory function, bowel, and bladder function). As a consequence, symptoms like fatigue, cognitive disturbances, and depression are not well-reflected in this categorization, although they are frequent and highly influential on quality of life on an individual level (14). This shortcoming can be seen in the wide ranges of the disability weights within EDSS-based disease severity subgroups, particularly in the sensitivity analysis based on utility data from the SMSR.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the generally higher utility, their impact on the population burden is likely to be small as well. Next, the use of an EDSS-proxy instead of a clinically assessed EDSS is expected to only marginally affect the estimates because categorizations and not exact EDSS values are used and a previous study showed a good accuracy of the EDSS-proxy (14). Another source of uncertainty concerns the mortality within the context of MS since the details of mortality recording vary substantially in different mortality registries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been estimated that the average disease duration from diagnosis to use of a permanent walking aid is ~13 years ( 8 ). In fact, these motor problems have recently been identified by MS patients as the symptoms most undermining their health-related quality of life (HRQoL) ( 9 ).…”
Section: Introductionmentioning
confidence: 99%